2004
DOI: 10.1103/physreva.70.062302
|View full text |Cite
|
Sign up to set email alerts
|

Quantum computing using single photons and the Zeno effect

Abstract: Abstract:We show that the quantum Zeno effect can be used to implement several quantum logic gates for photonic qubits, including a gate that is similar to the squareroot of SWAP operation. The operation of these devices depends on the fact that photons can behave as if they were non-interacting fermions instead of bosons in the presence of a strong Zeno effect. These results are discussed within the context of several no-go theorems for non-interacting fermions or bosons.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
189
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 200 publications
(190 citation statements)
references
References 41 publications
1
189
0
Order By: Relevance
“…In a similar way, it can be shown that the electric field at frequency 2 ω inside the resonator and just after the lower input coupling is given by…”
Section: Quasi-static Analysismentioning
confidence: 85%
See 3 more Smart Citations
“…In a similar way, it can be shown that the electric field at frequency 2 ω inside the resonator and just after the lower input coupling is given by…”
Section: Quasi-static Analysismentioning
confidence: 85%
“…Figure 9 shows the ratio of the self two-photon absorption rate S R to the cross two-photon absorption rate 2 R as a function of the difference in the two wavelengths in nm. It can be seen that the self two-photon absorption is a factor of 8 10 − smaller than the intended cross two-photon absorption for wavelength differences of 0.5 nm or more.…”
Section: Other Lossesmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence implementations of two-photon quantum protocols in integrated solid state device architectures are being enabled. For example, Zeno-type conditional coherent logic down to the single photon level becomes feasible in a monolithic nanoscale system [19][20][21][22] . Furthermore, charge redistribution or removal could be used to tune the lifetime of the optically-induced entangled state or to convert the optical entanglement into a hybrid or pure particle entanglement, resulting in potential quantum memory technology for single and entangled photons 14,[23][24][25][26][27] as well as opening additional paths for spin-photon entanglement 28,29 .…”
mentioning
confidence: 99%